Plastic responses of sweet potato (Ipomea batatas L.) root anatomy in compacted soil conditions - Ali, Mamuda Umaru; Sakimin, Siti Zaharah; Puteh, Adam; Karam Singh, Daljit Singh; Nazli, Muhammad Hazim (2020)
The response of crops to abiotic stress largely depends on its root system architecture since the root is the first to sense abiotic stress prevailing in the soil media. This study was conducted to investigate the effect of soil compaction on the anatomy of sweet potato roots. A field experiment was conducted in March 2017. The treatments used consisted of three compaction levels (no-till, tilled once and tilled twice) and three varieties (Gendut, Kedudut, and Vitato). The treatments were in factorial combination; arranged in a split-plot design and replicated four times. Sampled roots were viewed under a binocular microscope (Olympus BCH) for anatomical studies. The collected data were subjected to analysis of variance (ANOVA) to determine the effect of the treatments and their interactions; using the general linear model; SAS software version 9.4. Differences among treatment means were compared using the least significant difference (LSD) at p ≤ 0.05. Results obtained, indicated cortex and root xylem diameters, root proliferation was decreased with increased compaction but root lignification was increased. Root structure was also influenced by varietal variation. However, the effect was not constant with varieties. In all the observed characters Kedudut and Gendut had the least and the highest mean values respectively. Gendut variety showed the highest ability to adapt to compacted soil. The decrease in anatomical features could lead to a decrease in yield as a result of possible restrictions in the uptake of soil water and nutrients.